Strategi Pengelolaan dalam Pembelajaran Bahasa Arab sebagai Bahasa Kedua - Rahmat Hidayat; Septiana Widi Pangesti (Journal on Education, 2023)
Arabic is one of the languages that are used widely in the world. Where Islam developed, Arabic also developed. The role of Arabic is so big because it is a religious language in this part of the world. Learning strategy is needed because it is an important part of learning. Learning strategies can help students understand the meaning explained by the teacher more quickly. In this article the researcher uses the library research method. And the data collection used is from various literature, journal notebooks, Google Scholar and other references. The ability to manage Arabic learning is needed by teachers when teaching Arabic. Because he is the key to the success of the process of learning Arabic. And achieving the goals of learning Arabic is largely determined by the learning method. A teacher must be able to manage the Arabic learning process in terms of selecting methods, applying methods, managing classes, and using learning media. The strategy for managing the Arabic language learning method is by mastering various methods that are in accordance with the character of the diversity of students in the class and in accordance with the material and skills of the Arabic language being taught.